Amikacin Induced Ototoxicity in an 8 Year Old Patient with UTI: A Case Report - Lisa Mathew Adackapara; Keerthana Chandrasekar (Journal of Global Pharma Technology, 2020)
Ototoxicity is an adverse drug reaction of Amikacin and involves mainly bilateral high-frequency sensorineural hearing loss and tinnitus. This case report is essential to identify, resolve and create awareness of the predisposing factors which can lead to ototoxicity. It elaborates the rare adverse effect caused due to Amikacin induced ototoxicity and the treatment strategies adopted at a secondary care hospital in an 8 year old male child. Treatment for Urinary Tract Infection (UTI) included Amikacin for 1 day following which the next day he developed blocked ears and diminished hearing as an adverse reaction to the aminoglycoside antibiotic. Management emphasis is on prevention, as most hearing loss is irreversible. After 3 days of treatment, the patient’s condition improved and was discharged with advice to continue liquid paraffin 3drops-0-3drops in both ears for 3 days. Appropriate measures must be put into place to manage aminoglycoside-induced cochleotoxicity effectively, in order to maximize the affected individual’s quality of life.